2019
DOI: 10.18823/asiatefl.2019.16.3.10.927
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Development of English Learners’ Understanding of the Discussion Genre

Abstract: This study used a genre-based approach within a systemic functional linguistics (SFL) framework to assess the development of English learners' understanding of the discussion genre. Fifty-two undergraduates participated in a semester-long course, divided into three groups by English proficiency level. They were administered surveys at the beginning and end of the semester to assess their choice of appropriate lexicogrammatical features. A structural move analysis of their pre-and post-discussion genre writing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…These analyses also improved EFL learners' competence in writing a discussion text. A research result revealed that genre-based teaching improved the students' choices of lexicogrammatical features in a discussion text (Nagao, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These analyses also improved EFL learners' competence in writing a discussion text. A research result revealed that genre-based teaching improved the students' choices of lexicogrammatical features in a discussion text (Nagao, 2019).…”
Section: Introductionmentioning
confidence: 99%